(untitled) (Experimental biology, 2021)
Artemisia L. (family Asteraceae Dumort.) have scientific and practical interest as a source of biologically active compounds – essential oils, organic, fatty acids, tannins and etc. This article presents the results of studies on the content and composition of essential oils in some endemic and limited range species of g. Artemisia L. (A. cina Berg.ex Poljak., A. karatavica Krasch. et Abolin.ex Poljakov, A. porrecta Krasch.ex Poljakov) which growing in south Kazakhstan. The extraction of essential oils carried out by hydrodistillation method on a Clevenger apparatus. Chemical constituents of essential oils in for the first time studied plant species belong to g. Artemisia L. from south Kazakhstan determined on an Agilent 5975T LTM GC / MS / FID at the central laboratory of aromatic plants at Akdeniz University (Turkey, Antalya, 2019). Fifteen compounds were found and identified in essential oil of A. cina where 1,8-cineole (more than 60%) and thujone derivatives (8-14%) predominate. A. karatavica essential oil represented by 25 compounds where 1,8-cineole (50%) and camphor (22%) prevail. In the essential oil of A. porrecta 12 compounds were found where thujone derivatives (more than 75%), 1,8-cineole (8.2%) and camphor (7.6%) predominate. Most of the identified components belong to monoterpenes and nine compounds (sabinene, β-myrcene, α-terpinene, 1,8-cineole, γ-terpinene, p-cymene, α- and β-thujone, terpinen-4-ol) were found in all studied samples. A high content of 1,8-cineole (61.7 and 50.2%) is observed for the A. cina and A. karatavica samples which is consistent with the literature data. The indicators of essential oils of the studied plants may play 1,8-cineole, thujone derivatives and camphor the total content of them in the essential oils is more than 70% which makes possible to recommend the studied species of wormwood for further investigation as a potential sources of plant raw materials for creating preparations with antibacterial, antifungal and antitumor activities.